Educação de jovens e adultos em espaços religiosos: escolhas, negociações e conflitos - Heli Sabino de Oliveira (2012)
The present study describes and analyzes the Youth and Adults Education (EJA) in religious spaces, linked tothe Municipal Network Education of Belo Horizonte (RME/BH). When inquiring about the limits and possibilities of educational services, reconstitute the trajectory of EJA in the city of Belo Horizonte, amphasizing the agreements, conflicts and alliances between established social and political actors who acted and act in this educational modality. We found that the emergence of EJA classes out of school results from the confluence of economic and political interests that mark the history of Youth and Adults Education in that city. We observe that the educational spaces of religious groups that give room for RME/BH are not neutral. His architectural arrangements, their signs, their images are linked to systems of meaning and representation of society and nature, seeking to forge social identities and religious individuals. The youth and adults education takes thus the marks of catholicism, pentecostalism, religions with African roots and spiritualism, as space is established. Placing much emphasis on relations between educators/students and the as the ways in which cultural memories are preserved and surveyed in EJA classes in religious spaces, emphasizing the materiality of the teaching provided. With the background of the Cultural Studies perspective, we take the youths and adults education, religiousness and teaching as cultural practices, situated in an arena of competition for conflicting meanings and representations. Assuming that the empirical data are not just reflections of sensory observation, but the result of application of certain theoretical concepts introduce the concepts of popular culture, religion and social identity as multifaceted categories, establishing meanings and senses giving intelligibility to social actions. To support the man concepts used in this thesis, we use, among other researches, studies of Stuart Hall, Homi Bhabha, Tomaz Tadeu da Siva and Luiz Alberto Oliveira Gonçalves and Ines Gonçalves Teixeira. The persons and spaces surveyed were selected from a sociocultural questionnaire applied to al teachers working in EJA classes in religious spaces. We look for spaces marked by religious otherness, ie, places where the teacher religiosity did not match the space in which religion exercised their teaching. Through semi-structured inteview, collect testimony from a forme coordinator of the Youth and Adult Education of the City Department of Education, five religious leaders (two pastors, a priest, counsel or and a militant spirit of the movement black an entity that coordinates the fight against prejudice ethno- racial and religious intolerance of religions of African origin) and four women teachers and teacher man. We found that the educationai policy of the Municipal Network does not take into account the profound changes now because the reigious field in Brazil in recent decades bring. By leaving a legacy to be, to become a choice, religion has become a market of symbolic goods, marked by the struggle for meaning and representation of the world and nature, creating new tensions and social conflicts. Formed in the struggle with other ideals, establishing religious identity on the one hand, sociability, feelings of community ties and cultural roots, on the other hand, tends to demarcate the differences, creating to some extent, forbidden to interfere in the educational process. This fact raises new questions to the educational process that can treat with contempt, fear and hostility to religious beliefs and identities are not hegemonic, classifying the different as inferior or dangerous as well as Iegitimizing certain religious practices over others In a multicultural context, studies on the relationship between religion and education can contribute to the formation of educators aware of the relational and performative aspects of identity construction, which would question the power relations which deepens the cultural distance between "them" and " us."